Development and Validation of Matrix Interference Method for Estimation of Miconazole Nitrate, Clobetasol Propionate in Combined Pharmaceutical Dosage Form - Abhijeet Welankiwar; Mrunmayee Kulkarni; Dehuti Fate; Dipti Ruikar; Dipti Bonde (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Matrix interference caused by excipients and preservatives can affect the accuracy and reliability of analytical methods used for the estimation of active pharmaceutical ingredients (APIs) in combined pharmaceutical dosage forms. Therefore, evaluation of matrix effects is essential for ensuring accurate quantitative analysis. Aim: The present study aimed to develop and validate a simple, rapid, and economical UV spectrophotometric method for evaluating matrix interference in a topical formulation containing Miconazole Nitrate, Clobetasol Propionate, and Chlorocresol. Methods: Standard and sample solutions were prepared using methanol and analyzed by UV spectrophotometry at the respective λmax values of Miconazole Nitrate (272 nm), Clobetasol Propionate (239 nm), and Chlorocresol (283 nm). Matrix interference was assessed using the standard addition method and recovery studies at 80%, 100%, and 120% levels. The method was validated according to ICH Q2 (R1) guidelines for linearity, accuracy, precision, specificity, limit of detection (LOD), and limit of quantification (LOQ). Results and Discussion: The developed method demonstrated excellent linearity with correlation coefficients (R²) greater than 0.999 for all analytes. Assay values for Miconazole Nitrate and Clobetasol Propionate were found to be 99.37% and 100.20%, respectively. Recovery studies showed satisfactory results, indicating negligible matrix interference. Precision studies exhibited %RSD values below 2%, confirming good repeatability and reproducibility. Low LOD and LOQ values indicated adequate sensitivity of the method. Conclusion: The validated UV spectrophotometric method was found to be accurate, precise, sensitive, and suitable for routine quality control analysis of combined pharmaceutical dosage forms with minimal matrix interference.a